A study on laser beam oscillating welding characteristics for the 5083 aluminum alloy: Morphology, microstructure and mechanical properties. (May 2020) - Li, Shangren; Mi, Gaoyang; Wang, Chunming
Highlights: Beam oscillation improves the morphology of the weld surface but reduces penetration depth. Beam oscillation reduces welding porosity and refines grains in the weld fusion zone. The tensile strength and micro-hardness of oscillating welds are improved. Abstract: Laser beam oscillating welding was used to connect 5083 aluminum alloy sheets. The effect of oscillating parameters on the weld porosity and morphology was investigated. When the oscillating frequency was over 200 Hz and the oscillating diameter was over 2 mm, the weld porosity could be suppressed by laser beam oscillation. The microstructure analysis conducted by electron backscattered diffraction and an electron probe micro-analyzer revealed that the laser beam oscillation could refine grains and promote the uniform distribution of the β(Mg2 Al3 ) phase in the weld fusion zone, thus leading to increasing micro-hardness of the weld zone. The tensile test results demonstrated that the tensile strength and the elongation of the laser oscillating welding joints were much higher than the joints without oscillation, mainly owing to the suppression of porosity.